Characteristics and parameter extraction for NiGe/n-type Ge Schottky diode with variable annealing temperatures - 刘红侠 吴笑峰 胡仕刚 石立春 (Chinese physics B, 2010)
Current transport mechanism in Ni-germanide/n-type Ge Schottky diodes is investigated using current-voltage characterisation technique with annealing temperatures from 300 ℃ to 500℃. Based on the current transport model, a simple method to extract parameters of the NiGe/Ge diode is presented by using the I-V characteristics. Parameters of NiGe/n-type Ge Schottky diodes fabricated for testing in this paper are as follows： the ideality factor n, the series resistance Rs, the zero-field barrier height Фb0, the interface state density Dit, and the interracial layer capacitance Ci. It is found that the ideality factor n of the diode increases with the increase of annealing temperature. As the temperature increases, the interface defects from the sputtering damage and the penetration of metallic states into the Ge energy gap are passivated, thus improving the junction quality. However, the undesirable crystallisations of Ni-germanide are observed together with NiGe at a temperature higher than 400℃. Depositing a very thin （-1 nm） heavily Ge-doped n＋ Ge intermediate layer can improve the NiGe film morphology significantly.